Regional economics - Capello, Roberta (London, 2007)
A vast amount of theories and models have been developed since the official recognition of regional economics as a distinct branch of economics. In particular, this book focuses on logical and theoretical linkages between different theories and models: both macro and microeconomic; neoclassical and Keynesian. The evolution of theoretical approaches in regional economics is dealt in the book through the evolution of the concept of space: from physical space, which characterizes location theory, to uniform space (typical of neoclassical and Keynesian approaches ) to diversified-relational space (embedded in local districts and milieu approaches, as well as in the theory of learning regions) to diversified stylised space (as exemplified by the new economic geography and dynamic neoclassical approaches).
Keywords: Economics